2022
DOI: 10.3346/jkms.2022.37.e47
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Hospital Delay in Patients With Acute Stroke During the Initial Phase of the Coronavirus Disease 2019 Outbreak

Abstract: Background When a sudden outbreak of an infectious disease occurs, emergency medical services (EMS) response could be negatively affected. The poor prognosis of acute stroke may be largely attributed to delays in treatment. This study aimed to identify the impact of the sudden outbreak of coronavirus disease 2019 (COVID-19) on EMS response for patients with acute stroke. Methods This comparative cross-sectional study was conducted in 25 safety centers in Seoul, Korea. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Despite the excellent outcome of Korea's quarantine measures, there have been reports of increased mortality due to specific causes or delayed treatment during the COVID-19 pandemic [12][13][14][15]. When mortality rates were analyzed by separating them by deaths in medical facilities and deaths outside of medical facilities, a significant increase in deaths outside of medical facilities was observed in 2020.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the excellent outcome of Korea's quarantine measures, there have been reports of increased mortality due to specific causes or delayed treatment during the COVID-19 pandemic [12][13][14][15]. When mortality rates were analyzed by separating them by deaths in medical facilities and deaths outside of medical facilities, a significant increase in deaths outside of medical facilities was observed in 2020.…”
Section: Introductionmentioning
confidence: 99%
“…At the end of 2020, the government secured around 6,000 beds in infectious disease hospitals and supported the deployment of medical and paramedical personnel[31], which may disrupt existing medical care. Delays in the management of patients with acute stroke or acute myocardial infarction during the pandemic were reported[14,15, 32].Additionally, longer or delayed emergency transfer times were noted[33]. In particular, in the case of fever with sepsis, emergency transportation was sometimes refused[34].…”
mentioning
confidence: 99%
“… Clinical Outcomes 57 Seo et. al 69 Pre-Hospital Delay in Patients With Acute Stroke During the Initial Phase of the Coronavirus Disease 2019 Outbreak Cohort Patient care reports Seoul, KR ● In the initial phase after the Covid-19 outbreak, EMS response times for acute strokes were delayed. ● Clinical outcomes of patients with acute stroke deteriorated.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have verified the impact of COVID-19 on transport interval for acute stroke, acute myocardial infarction, and out-of-hospital cardiac arrest patients. 5 6 7 Early in the COVID-19 pandemic, studies reported that ED transport was delayed and paralyzed due to the explosion in emergency calls by patients with fever or dyspnea due to the rapid spread of coronavirus in some cities, such as New York and Milan. 8 9 10 11 Korea had a low incidence of COVID-19 before omicron emergence; the situation in Korea was different from that in these cities.…”
Section: Introductionmentioning
confidence: 99%